2013
DOI: 10.1002/jmri.24203
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac volumes using an isotropic whole‐heart dual cardiac phase sequence in pediatric patients

Abstract: The 3D DP technique provides as accurate cardiac volumes as the 2D SSFP technique in the pediatric population, but with the added benefits of easier data acquisition and detailed anatomical information of the whole heart and great vessels in a single free-breathing scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
1
10
2
Order By: Relevance
“…This study demonstrated that the stroke volumes calculated from the ventricular volumes had good correlations with the arterial flow volumes measured by the phase-contrast MRI (the reference standard), slightly higher for the 2D cine MRI than for the 3D whole-heart MRI ( Table 2 ). Noteworthy, the results of this study were different from others reporting ventricular volume quantification of 3D whole-heart MRI that displayed comparable or higher correlations and reproducibility with those of flow measurements or 2D short-axis cine MRI ( 5 6 7 ). Instead of 3D threshold-based segmentation used in this study that is a very accurate and reproducible method, less accurate methods were used in their studies, such as a deformable simplex mesh model for 3D whole-heart MRI ( 5 6 ) and a 2D threshold-based segmentation for both the reformatted 3D whole-heart MRI in short-axis plane and the 2D short-axis cine MRI ( 7 ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This study demonstrated that the stroke volumes calculated from the ventricular volumes had good correlations with the arterial flow volumes measured by the phase-contrast MRI (the reference standard), slightly higher for the 2D cine MRI than for the 3D whole-heart MRI ( Table 2 ). Noteworthy, the results of this study were different from others reporting ventricular volume quantification of 3D whole-heart MRI that displayed comparable or higher correlations and reproducibility with those of flow measurements or 2D short-axis cine MRI ( 5 6 7 ). Instead of 3D threshold-based segmentation used in this study that is a very accurate and reproducible method, less accurate methods were used in their studies, such as a deformable simplex mesh model for 3D whole-heart MRI ( 5 6 ) and a 2D threshold-based segmentation for both the reformatted 3D whole-heart MRI in short-axis plane and the 2D short-axis cine MRI ( 7 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Noteworthy, the results of this study were different from others reporting ventricular volume quantification of 3D whole-heart MRI that displayed comparable or higher correlations and reproducibility with those of flow measurements or 2D short-axis cine MRI ( 5 6 7 ). Instead of 3D threshold-based segmentation used in this study that is a very accurate and reproducible method, less accurate methods were used in their studies, such as a deformable simplex mesh model for 3D whole-heart MRI ( 5 6 ) and a 2D threshold-based segmentation for both the reformatted 3D whole-heart MRI in short-axis plane and the 2D short-axis cine MRI ( 7 ). Substantial underestimation of ED volumes, especially for the RV, quantified by using the 3D whole-heart MRI in this investigation seemed to be chiefly caused by early timing of the ED phase in spite of the longest trigger delay.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This was mainly due to the length of the protocol. Nevertheless, it has been previously shown that the dual cardiac phase technique provides accurate cardiac volume assessment in adult [8] and pediatric patients with congenital heart diseases [22].…”
Section: Limitations Of the Studymentioning
confidence: 99%